Venture Capitalist's Screening Process: Analysing the importance of different screening criteria for early stage ventures (Part of the East Midlands Early Growth Fund Internship Project) - Sajwan, Varun (2009)
This report is a part of the group management project done with East Midlands Early Growth Fund. It looks at the various initial screening criteria of early stage venture capitalists and analyses the importance of each of those criteria used in the assessment of start-ups and early stage ventures. The 5 shortlisted companies from the group management project are further analysed here with respect to the initial screening criteria applied to each. The importance of each criterion in selecting those companies is given in detail. This report also looks at past studies undertaken in the field of screening criteria for early stage ventures. The report goes on to conclude that some initial screening criteria are more important than others and gives recommendations to both the venture capitalists and the entrepreneurs regarding the importance of initial screening criteria for both of them. This report finally provides the limitations under which this research was undertaken and the future research possibilities that arise out of those limitations.